ANALISIS PENGARUH PROFITABILITAS, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Asri Khayati; Deni Ramdani (Politeknik Bisnis Indonesia, 2021)
The company's long-term goal is to achieve maximum company value, which will affect the confidence of investors to invest some of their funds in the company. Corporate funding is significant for the company's operational activities and involves many parties who support the company's business activities. Good funding decisions are reflected in the composition of the capital structure so that it needs to be appropriately managed. This research aims to gain further theoretical knowledge regarding the effect of profitability, liquidity, and firm size on capital structure. This research is quantitative. The population in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2017-2019. The data analysis technique in this study used multiple linear regression analysis with SPSS software. Based on the analysis results, it is concluded that the profitability variable (X1) has a negative and significant effect on the capital structure (Y). Meanwhile, the liquidity variable (X2) and firm size (X3) do not affect the level of the company's capital structure (Y).